Congestion costing critique. Critical evaluation of the "Urban Mobility Report". - Litman, Todd (My University, 2013)
The Urban Mobility Report (UMR) is a widely-cited study that quantifies and monetizes traffic congestion costs in U.S. metropolitan regions. The report critices the UMR's assumptions and methods, that refers only to automobile travel and ignoring other forms of transportation.
Keywords: Individualverkehr; Fahrradverkehr; Stadtverkehr; Verkehrsbelastung; Autoverkehr; Kostenanalyse; Verkehrskosten; Evaluation; Multimodalität